2011
DOI: 10.1073/pnas.1104391108
|View full text |Cite
|
Sign up to set email alerts
|

C terminus of Hsc70-interacting protein (CHIP)-mediated degradation of hippocampal estrogen receptor-α and the critical period hypothesis of estrogen neuroprotection

Abstract: Recent work suggests that timing of 17β-estradiol (E2) therapy may be critical for observing a beneficial neural effect. Along these lines, E2 neuroprotection, but not its uterotropic effect, was shown to be lost following long-term E2 deprivation (LTED), and this effect was associated with a significant decrease of estrogen receptor-α (ERα) in the hippocampus but not the uterus. The purpose of the current study was to determine the mechanism underlying the ERα decrease and to determine whether aging leads to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
132
1
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 127 publications
(141 citation statements)
references
References 43 publications
7
132
1
1
Order By: Relevance
“…These data also support the hypothesis that ER␤ signaling in response to E2 is drastically altered by age, as the expression levels of these proteins did not significantly correlate with changes in protein-protein interaction. In this study there were no significant changes in ER␤ protein levels with age or E2 treatment, and this is consistent with a similar report that recently demonstrated no age or E2 deprivation effects on ER␤ expression (24). E2 deprivation or replacement decreased ER␤ expression in 24-month-old but not 18-month-old rats (20 -24).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…These data also support the hypothesis that ER␤ signaling in response to E2 is drastically altered by age, as the expression levels of these proteins did not significantly correlate with changes in protein-protein interaction. In this study there were no significant changes in ER␤ protein levels with age or E2 treatment, and this is consistent with a similar report that recently demonstrated no age or E2 deprivation effects on ER␤ expression (24). E2 deprivation or replacement decreased ER␤ expression in 24-month-old but not 18-month-old rats (20 -24).…”
Section: Discussionsupporting
confidence: 81%
“…S-nitrosylation of GAPDH initiates apoptosis by translocating to the nucleus and interacting with Siah1 (an E3-ubiquitin ligase), also known as BAG-1. BAG-1 has been shown to interact with ER␣ and facilitate the down-regulation of estrogen receptors over extended periods of E2 deprivation (24). Overall, the role for a nuclear interaction between ER␤ and GAPDH is not yet clear, but a change in this interaction could dysregulate the balance between E2 neuroprotection and apoptosis in aged animals.…”
Section: Discussionmentioning
confidence: 99%
“…Other investigators have reported similarly detrimental effects of long-term ovariectomy on the ability of chronic E 2 to enhance spatial working memory , supporting the idea that long-term hormone deprivation impairs E 2 's capacity to facilitate hippocampal synaptic plasticity and memory. The reasons for this decreased responsiveness are not yet clear, but could be due to ubiquitination and degradation of estrogen receptors as observed in the CA1 of long-term ovariectomized rats (Zhang et al 2011).…”
Section: Synaptic Plasticitymentioning
confidence: 99%
“…25 For these women, there was no long-term effect of HT on cognition, either positive or negative. Another area of work is related to estrogen receptor binding that may explain how neuroprotective effects of estrogen may erode with aging 26,27 ; however, these do not explain why CEE therapy may adversely affect brain volumes in older women.…”
mentioning
confidence: 99%